A PUF Hub Drives Self-Renewal in Caenorhabditis elegans Germline Stem Cells - Haupt, Kimberly A. (Genetics, 2020)
Stem cell regulation relies on extrinsic signaling from a niche plus intrinsic factors that respond and drive self-renewal within stem cells. A priori, loss of niche signaling and loss of the intrinsic self-renewal factors might be expected to have equivalent stem cell defects. Yet this simple prediction has not been borne out for most stem cells, including Caenorhabditis elegans germline stem cells (GSCs). The central regulators of C. elegans GSCs include extrinsically acting GLP-1/Notch signaling from the niche; intrinsically acting RNA-binding proteins in the PUF family, termed FBF-1 and FBF-2 (collectively FBF); and intrinsically acting PUF partner proteins that are direct Notch targets. Abrogation of either GLP-1/Notch signaling or its targets yields an earlier and more severe GSC defect than loss of FBF-1 and FBF-2, suggesting that additional intrinsic regulators must exist. Here, we report that those missing regulators are two additional PUF proteins, PUF-3 and PUF-11. Remarkably, an fbf-1 fbf-2; puf-3 puf-11 quadruple null mutant has a GSC defect virtually identical to that of a glp-1/Notch null mutant. PUF-3 and PUF-11 both affect GSC maintenance, both are expressed in GSCs, and epistasis experiments place them at the same position as FBF within the network. Therefore, action of PUF-3 and PUF-11 explains the milder GSC defect in fbf-1 fbf-2 mutants. We conclude that a “PUF hub,” comprising four PUF proteins and two PUF partners, constitutes the intrinsic self-renewal node of the C. elegans GSC RNA regulatory network. Discovery of this hub underscores the significance of PUF RNA-binding proteins as key regulators of stem cell maintenance.